Hereditary angioneurotic oedema: a neglected diagnosis. - Morris, G E (1987)
A case of hereditary angioneurotic oedema, which was only diagnosed after presentation to several hospital departments, is reported. It was then discovered that the mother of the patient had the same condition but that, unusually, it appeared to have been in remission for more than 20 years. This disease, due to C1 esterase inhibitor deficiency, is potentially fatal but easily treatable. The diagnosis is often missed.